Blood Pressure Parameters among Smokers and Smokeless Tobacco Users in a Tertiary Level Hospital in Bangladesh (Update Dental College Journal, 2013)
In Bangladesh, use of different kinds of smokeless tobacco and smoking is common among adult men. The study aimed to assess blood pressure parameters among adult male smokers and smokeless tobacco users as data on related field is limited and inclusive. For this study, 105 male respondents were selected from outdoor department of Dhaka Medical College Hospital. Among them, 30 were smokeless tobacco users and 75 were smokers. All data were recorded in data collection form. Statistical analysis of results between the groups were calculated by using unpaired students't' test. In this study, the mean (±SD) of systolic blood pressure was 154.50±26.79 mm of Hg in Group A and 151.67±19.24 mm of Hg in group B respectively. The mean (±SD) of diastolic blood pressure was 96.67±10.93 mm of Hg in Group A and 86.47±14.74 mm of Hg in group B respectively. The mean (± SD) of diastolic blood pressure was significantly higher (P